2021
DOI: 10.1038/s41598-021-90268-6
|View full text |Cite
|
Sign up to set email alerts
|

Abandonment and rapid infilling of a tide-dominated distributary channel at 0.7 ka in the Mekong River Delta

Abstract: The Ba Lai distributary channel of the Mekong River Delta was abandoned and infilled with sediment during the Late Holocene, providing a unique opportunity to investigate the sediment fill, timing and mechanisms of channel abandonment in tide-dominated deltaic systems. Based on analysis and age dating of four sediment cores, we show that the channel was active since 2.6 ka and was abandoned at 0.7 ka as marked by the abrupt disappearance of the sand fraction and increase in organic matter and sediment accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…It is also possible that a partial connection to the deltaic system was still present, but this had likely been reduced to the point that only the mud fraction was being supplied from upstream. Instead, it is suggested that most of the sediment infilling this abandoned channel would be supplied from its mouth by the action of tidal currents, after being transported to the shelf mainly by channels located north‐eastward of the Ba Lai palaeochannel (Tamura et al ., 2012; Gugliotta et al ., 2021). This is consistent with the general dynamics of the present‐day MRD, with sediment being exported by the channels during high flow and partially reimported from the shelf during low flow (Nowacki et al ., 2015; Gugliotta & Saito, 2019; Jiang et al ., 2020), and with a longshore net sediment transport towards the south‐west (Fang et al ., 2006; Tamura et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is also possible that a partial connection to the deltaic system was still present, but this had likely been reduced to the point that only the mud fraction was being supplied from upstream. Instead, it is suggested that most of the sediment infilling this abandoned channel would be supplied from its mouth by the action of tidal currents, after being transported to the shelf mainly by channels located north‐eastward of the Ba Lai palaeochannel (Tamura et al ., 2012; Gugliotta et al ., 2021). This is consistent with the general dynamics of the present‐day MRD, with sediment being exported by the channels during high flow and partially reimported from the shelf during low flow (Nowacki et al ., 2015; Gugliotta & Saito, 2019; Jiang et al ., 2020), and with a longshore net sediment transport towards the south‐west (Fang et al ., 2006; Tamura et al ., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with the general dynamics of the present‐day MRD, with sediment being exported by the channels during high flow and partially reimported from the shelf during low flow (Nowacki et al ., 2015; Gugliotta & Saito, 2019; Jiang et al ., 2020), and with a longshore net sediment transport towards the south‐west (Fang et al ., 2006; Tamura et al ., 2010). The consistent ages and high sediment accumulation rates for the abandoned‐channel fill suggest that the channel was abandoned abruptly at approximately 0.7 ka and infilled rapidly in the order of decades to a few centuries (Gugliotta et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations